THE BURDEN OF QUARANTINE ON MENTAL HEALTH AMIDST COVID-19 PANDEMIC: A CROSS SECTIONAL STUDY - Taimoor Ashraf Khan (Army Medical College Rawalpindi, 2020)
Objective: To gauge the frequency of post traumatic stress disorder, stress, anxiety and depression amongst the general population that has been quarantined in public quarantines.